NILAI-NILAI PANCASILA SEBAGAI FALSAFAH PANDANGAN HIDUP BANGSA UNTUK PENINGKATAN KUALITAS SUMBER DAYA MANUSIA DAN PEMBANGUNAN LINGKUNGAN HIDUP - Nugroho, Iwan (Jurnal Konstitusi, 2010)
Pancasila as the nation´s view of life need to be implemented in a real life. This has been implemented by the founding fathers through a hard work and struggle resulting in the independence of Indonesia. At present, the values of Pancasila philosophy is very important to produce quality human beings, who have a strong character in spirituality, self confidence, and high work ethic to support national development. This paper attempts to describe it through the improvement of human resources in the environmentally sustainable development. At the level of state administrators, the high quality of human resources is shown in the formulation of regulations or policies in strengthening the functions of state institutions, local autonomy and natural resource management. At the level of economic actors or society, quality human resources is in line with the increase of economic welfare in the field of urban development, ecotourism and infrastructure. These high quality of human resources are responsible to realize prosperity in enhancing human dignity as a nation.